Effect of mineral nitrogen and organics on growth and yield of rice (Oryza sativa L.) in Typic Ustifluvents soil - Kaviya, R; Manivannan, R; Senthilvalavan, P; Kalaisudarson, S (Plant Science Today, 2025)
Rice (Oryza sativa L.) is a staple food for nearly half of the world's population. To meet the global demand of growing population, rice production must be substantially increased with the adoption of Integrated Nutrient Management (INM). With this background, present field study was conducted in 2023 at a farmer’s holding in Kuttalam to evaluate the effect of organics alone or mineral nitrogen alone or in combination tested on an N-equivalent basis on sandy clay loam soil (Padugai series- Typic Ustifluvents). The research was conducted during Samba season (Oct- Feb. 2023) using a randomized block design with three replications. Rice variety was used as the test crop, with ten treatments consisting of Nitrogen applied on an equivalent basis with organic manures, inorganic fertilizers and a control. Based on N equivalent basis, the required quantities of organic manures were applied to rice. Observations on growth parameters viz. (plant height, tiller count, leaf area index, chlorophyll content, crop growth rate (CGR), relative growth rate (RGR), net assimilation rate (NAR), grain and straw yield were recorded and the data were analysed using LSD at 5 % probability level for significant differences. The results revealed that the application of 75 % RDN (urea) combined with 25 % N (poultry manure) (T7) achieved the highest growth parameters grain yield and straw yield in rice, Where the lowest values were recorded in the control (T1). The findings demonstrate that a combined application of mineral nitrogen and organic fertilizers is required to achieve the maximum rice yield.